2019
DOI: 10.1002/cctc.201801555
|View full text |Cite
|
Sign up to set email alerts
|

Carbon with Surface‐Enriched Nitrogen and Sulfur Supported Au Catalysts for Acetylene Hydrochlorination

Abstract: What prompted you to investigate this topic?Carbon-supported gold catalysts have the potential to replace the toxic mercuric chloride-baseds ystem that already applied industrially in acetylene hydrochlorination. However, the existence of complex nitrogen species on carbon surfacee ssentially hinderst he assessment of the nature of the active site. In this respect, an efficient method, to adjustt he nitrogen speciation, is necessary for the sustainable expansion of the technology.W eh erein introduce an innova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…To clarify the interaction between N‐containing functional groups and CuNi species in this work, the XPS fine spectra in N 1s region has been also scanned (Figure 6D). The N 1s high‐resolution spectrum of rss AC revealed that there were three peaks located at 398.4, 400.1, 407.5 eV corresponding to the pyridinic‐N, pyrrolic‐N and oxidized‐N [45] . The corresponding peaks of CuNi/ rss AC have been centered at 399.0, 400.8 and 407.5 eV.…”
Section: Resultsmentioning
confidence: 98%
“…To clarify the interaction between N‐containing functional groups and CuNi species in this work, the XPS fine spectra in N 1s region has been also scanned (Figure 6D). The N 1s high‐resolution spectrum of rss AC revealed that there were three peaks located at 398.4, 400.1, 407.5 eV corresponding to the pyridinic‐N, pyrrolic‐N and oxidized‐N [45] . The corresponding peaks of CuNi/ rss AC have been centered at 399.0, 400.8 and 407.5 eV.…”
Section: Resultsmentioning
confidence: 98%
“…Recently, single atomically dispersed catalysts (also called single-atom catalysts, SACs) have emerged as a cutting-edge field in heterogeneous catalysis, not only due to their 100% atomic utilization efficiency but also due to their outstanding catalytic performance in water splitting, oxygen reduction, acetylene hydrochlorination, and other heterogeneous catalytic reactions. , Generally, the strong interaction between ligands and metals plays a key role in segregating, dispersing, and stabilizing single metal-atoms and further affects the catalytic behavior of metal-sites. Currently, the structures of metals, including coordination environment, binding modes, and oxidation state regulation induced by the defects or/and functions on the supports, remain a great challenge to the synthesis and regulation of SACs. Meanwhile, very few studies have been performed to unveil the catalytic features and mechanisms on vacancy-defect sites, suggesting the necessity to determine how these sites with different structures catalyze the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[ 29–31 ] Subsequently, numerous studies have been carried out to improve the stability of gold chloride by adding other additives. [ 32–42 ]…”
Section: Introductionmentioning
confidence: 99%